Characters and magic signs in the Picatrix and other Medieval magic texts - Láng, Benedek (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The word „characters” covers a number of different phenomena in the Middle Ages. It might refer to a list of incomprehensible signs and astrological symbols inscribed in a talismanic sigil, to a series of Latin letters used for magical purposes, and also to a written form of verbal incantation, a written charm. Characters were often used in the field of talismanic or celestial magic in order to name spiritual beings. The paper reviews the use of characters in various medieval sources: textual amulets, necromantic manuals, texts on talismanic magic and the most famous medieval magical summary, the Picatrix.